A Framework Coupling VISSIM and OMNeT++ to Simulate Future Intelligent Transportation Systems - Tibor Petrov; Ilya Finkelberg; Nina Zarkhin; Peter Počta; Ľuboš Buzna; Ayelet Gal-Tzur; Tatiana Kováčiková; Tomer Toledo; Milan Dado (Communications - Scientific letters of the University of Zilina, 2021)
With the spread of connected vehicles (CVs), a growth of novel information services exploiting data transmitted by CVs is expected. Wireless communication systems, in particular in vehicular applications, operate with a varying level of transmission reliability, which may affect the quality of V2X-data-driven intelligent transport systems (ITS). Therefore, the performance of ITS should be evaluated in a variety of conditions and the configuration of parameters should be fine-tuned in a safe testbed, using computer simulations. A simple framework is presented, which couples VISSIM traffic simulation and OMNeT++ communication networks simulation in real time, enabling an assessment of the relationship between a communication reliability and transport service quality. A functionality of the framework is demonstrated by applying it to a scheme controlling signalized intersections while estimating traffic flows from the V2I data.